The art of Miyazaki's Spirited away - Oniki, Yuji; Lu, Alvin 1969-; Miyazaki, Hayao 1941-; Sutajio Jiburi, Kabushiki Kaisha (San Francisco, California Viz Communications, Inc., 2002)
Provides sketches, backgrounds, and character designs from the film "Spirited away" and includes information about the making of the film as well as the screenplay.
Hayao Miyazaki concept sketch collection -- Concept art, backgrounds, character designs -- The making of computer graphic digital images -- Screenplay.
All concept sketches by Hayao Miyazaki ; concept art by Yoji Takeshige.
Keywords: Sen to Chihiro no kamikakushi (Motion picture).; Animation (Cinematography) -- Japan; Animated films -- Japan -- Technique; Animated films -- Japan; Fantasy films -- Japan; Animation (Cinematography); Animated films -- Technique; Motion pictures. -- Art direction